‘Terrorist’ labelling, counterterrorism actions and conflict dynamics: The case of contemporary armed conflict in northern Mozambique - Bathromeu Mavhura (Stellenbosch : Stellenbosch University, 2025)
Thesis (DPhil)--Stellenbosch University, 2025.